Procyanidins from the stem wood of Machilus japonica and their inhibitory effect on LDL oxidation - Park, Hee-Jung; Kim, Su-Yeon; Song, Na-Young; Cho, Jin-Gyeong; Kang, Ji-Hyun; Jeong, Tae-Sook; Lee, Dae-Young; Kim, Geum-Soog; Kim, Yong-Bum; Kang, Hee-Cheol; Baek, Nam-In (Archives of pharmacal research, 2014)
The stem wood of Machilus japonica Siebold & Zucc were extracted with 80 % aqueous MeOH, and the concentrated extract was successively partitioned with ethyl acetate (EtOAc), normal butanol, and water. From the EtOAc fraction, five procyanidins, procyanidin A1 ( 1 ), procyanidin A2 ( 2 ), procyanidin B7 ( 3 ), cinnamtannin B1 ( 4 ), and aesculitannin B ( 5 ), were isolated. Their chemical structures were identified through spectroscopic data analyses including NMR, MS, and IR. This is the first time any of these compounds have been isolated from this plant. The compounds were evaluated for inhibition activity on LDL oxidation. All of these compounds and the positive control, BHT, showed a very high inhibition effect with IC 50 values of 0.94, 2.1, 1.8, 1.1, 1.0, and 1.9 μM, respectively.